The Effect of Digital Marketing Strategy, Social Media Use, and Service Quality on Customer Loyalty at E-commerce Companies in Jakarta - Deysyelin Y.T.J. Wongkar; Dhety Chusumastuti; Hayu Lusianawati; Eva Yuniarti Utami; Widyatmoko Widyatmoko (Jurnal Multidisiplin West Science, 2024)
This research investigates the effect of digital marketing strategy, social media use, and service quality on customer loyalty within the context of e-commerce companies operating in Jakarta. A quantitative analysis was conducted with a sample of 150 participants, utilizing Structural Equation Modeling with Partial Least Squares (SEM-PLS 4). Descriptive statistics, measurement model evaluation, structural model results, and mediation analysis were employed to examine the interrelationships among the variables. The findings reveal significant positive relationships between digital marketing strategy, social media use, service quality, and customer loyalty. Furthermore, customer satisfaction was identified as a partial mediator between digital marketing strategy and customer loyalty. The model fit assessment indicates a robust fit, supporting the validity of the proposed structural model. The study provides practical implications for e-commerce companies in Jakarta, emphasizing the importance of holistic strategies that integrate digital marketing, social media, and service quality to enhance customer loyalty.